2020
DOI: 10.1149/1945-7111/abaae7
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective and Efficient Electrocatalytic Semihydrogenation of Diphenylacetylene in a PEM Reactor with Pt–Pd Alloy Cathode Catalysts

Abstract: Electric power can be generated from renewable energy sources such as solar and wind, making electrocatalytic hydrogenation an important technology to reduce carbon dioxide emissions in the organic synthesis industry. In the present work, the electrocatalytic semihydrogenation of diphenylacetylene was carried out in a proton exchange membrane (PEM) reactor with carbon-supported Pt, Pd, and Pt–Pd alloy cathode catalysts. Diphenylacetylene introduced into the PEM reactor at less negative potentials underwent ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The cell structure of the similar concept is schematically described elsewhere. 27 One of the biggest advantages of the cell is the spring behind the electrode on one side, which allows us to standardize the pressure for the stack of electrodes. The electrolyte for water electrolysis was 1.0 M K 2 CO 3 solution.…”
Section: Electrochemical Evaluation Of Her Performance Ofmentioning
confidence: 99%
“…The cell structure of the similar concept is schematically described elsewhere. 27 One of the biggest advantages of the cell is the spring behind the electrode on one side, which allows us to standardize the pressure for the stack of electrodes. The electrolyte for water electrolysis was 1.0 M K 2 CO 3 solution.…”
Section: Electrochemical Evaluation Of Her Performance Ofmentioning
confidence: 99%
“…Therefore, various applications of PEM reactor systems utilizing electrosynthetic processes, such as the reduction of toluenes (Takano et al, 2016;Fukazawa et al, 2018) and alkenes (Ogumi et al, 1981), and asymmetric hydrogenation of α,β-unsaturated acids (Fukazawa et al, 2020), have been reported (Raoult et al, 1984;Jorissen, 1996;Kishi et al, 2020;Fukazawa et al, 2021). In particular, the electrocatalytic hydrogenation of various alkynes in the PEM reactor is noteworthy because it allows for excellent product selectivity (Fukazawa et al, 2019;Nogami et al, 2020). It is worth mentioning that the hydrogenation reaction in the PEM reactor utilizes water as a proton source, enabling the avoidance of explosive hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…Other nickel complexes or nanoparticles have been reported to be good reduction catalysts, sometimes needing high hydrogen pressure and high temperature, [17–21] or an excess of the reductants, such as NaBH 4 or formic acid [22–26] . Hydrogen obtained from fossil resources can also be replaced by hydrogen produced electrochemically from water [5,27–30] . This approach is particularly important for deuteration reactions, as it allows isotopically labeled compounds, which have applications in medicinal chemistry, to be synthesized simply by using deuterated water solutions, without the need to use deuterium gas cylinders [31,32] .…”
Section: Introductionmentioning
confidence: 99%